Guanidines as reagents in proton-coupled electron-transfer reactions and redox catalysts - Himmel, Hans-Jörg (Synlett, 2018)
Redox-active guanidines are ideal proton-coupled electron-transfer (PCET) reagents, since they combine a high Brønsted basicity with a low and tunable redox potential. In this article, the development of redox-active guanidines (especially guanidino-functionalized aromatics, GFAs) in the last ten years is summarized, and their properties compared to other organic Brønsted bases and organic electron donors. First, some applications in organic chemistry that purely use the redox activity (formation of organic donor-acceptor materials and photochemical reductive C-C coupling reactions) are presented. Then, reactions that involve both proton and electron transfer are reviewed. In stoichiometric reactions, redox-active guanidines are used for the dehydrogenative coupling of thiols and phosphanes. The first redox catalytic applications are discussed, using dioxygen as green oxidizing reagent. 1 Introduction 2 Redox-Active Amines and Guanidines 3 Brønsted Basicity of Amines and Guanidines 4 Variations of GFA Compounds 5 GFA Compounds in Organic Donor-Acceptor Materials and as Reducing Reagents in Organic Synthesis 6 Stoichiometric Dehydrogenative Coupling Reactions with Redox-Active Guanidines 7 Guanidines as Redox Catalysts 8 Conclusions and Outlook
Gesehen am 15.01.2020